Bacterial patterns and antibiotics sensitivity in culture tests of diabetic foot ulcer - Raja Fauzan, Teuku; Mahfudz, Lauhil (Surgical Residency Program Syiah Kuala University, 2023)
Background: Diabetic foot ulcers are one of the complications of DM which can cause a decrease in productivity in patients. Diabetic ulcers make it easier for bacteria to grow and infect the body. Some pathogenic bacteria that are often found are Staphylococcus aureus, And Coli, Pseudomonas aeruginosa, Klebsiella pneumonia, and Proteus is wonderful. Antibiotics play an important role in the management of diabetic ulcers infected with bacteria, where the most sensitive antibiotics are Amikacin, Erythromycin, Meropenem, Ciprofloxacin, and Ampicillin. Therefore, this study aims to determine the bacterial patterns and bacterial sensitivity to antibiotics in diabetic ulcer patients in the surgical inpatient room of RSUDZA Banda Aceh. Method: This research is descriptive observational with a retrospective approach using medical record data from diabetic ulcer patients from August 2021 – August 2022. Sample collection was carried out randomly. non-probability sampling namely with total sampling. Data will be analyzed using univariate analysis Results: There were 60 samples of diabetic ulcer sufferers who underwent pus culture examination and antibiotic sensitivity testing in this study. Based on gender, men are the most likely to suffer from dibasic ulcers, namely 41 samples. The average age of diabetic ulcer sufferers was above 65 years in 19 samples. From the pus culture examination, it was found that the 4 most commonly found bacteria were: Staphylococcus aureus (13), E. Coli (13), Klebsiella pneumonia (10), and Pseudomonas aeruginosa (8). Based on the antibiotic sensitivity pattern, Meropenem has the strongest sensitivity to bacterial pneumonia and E. coli. Meanwhile, Levofloxacin has the strongest sensitivity to bacteria Staphylococcus aureus and Pseudomonas aeruginosa. Conclusion: It can be concluded that the cause of most diabetic ulcer infections are Staphylococcus aureus and E. Coli, while the antibiotics of choice are Meropenem and Levofloxacin because they have the highest sensitivity.